Agricultural and High-Density Polyethylene (HDPE) Waste Recycling to Produce High Voltage Insulator for Covered Conductor (CC) Distribution Systems - D. I. Moubarak; Mohamed E. Ibrahim; Amr M. Abd-Elhady; Didane, Djamal Hissein; Amin, Abdelazeem Abdelrahman (International Journal of Integrated Engineering, 2025)
Waste manufacturing represents a crucial technological field that finds a great interest all over the world. Therefore, recycling of agricultural and HDPE waste is carried out to produce high voltage insulator suitable for use in CC based electric distribution systems. The insulator manufacturing processes from the adopted waste are presented. To verify the suitability of the manufactured material to be used in producing high voltage insulator, the properties of the manufactured material are measured. These properties are material permittivity, dielectric loss, resistivity, tensile strength and water absorbance. The measured dielectric properties of the manufactured material are used to simulate an insulator with real dimensions to be compared with another traditional porcelain insulator with the same dimensions. The comparison is carried out from the electric field distribution point of view using finite element (FEM) analysis method. Also, the comparison is experimentally carried out using a real porcelain insulator and a manufactured insulator sample having the same creepage length. The experimental comparison is carried out though leakage current measurements considering wet polluted condition. Finally, the obtained results either theoretical or experimental show the validity of the manufactured insulator to be used efficiently in CC based electric distribution systems.